Enzyme‐immobilized reactors for rapid and efficient sample preparation in MS‐based proteomic studies. Issue 3 (14th January 2013) - Yamaguchi, Hiroshi; Miyazaki, Masaya; Dunn, Michael J.
<x xml:space="preserve">Abstract</x> Proteolysis is a key step in proteomic studies integrated with MS analysis but the conventional method of in‐solution digestion is limited by time‐consuming procedures and low sensitivity. Furthermore, obtaining reliable peptide maps and meaningful sequence data using MS analysis requires not only the separation of the digested peptides but also strictly defined proteolysis conditions. Recently, various immobilized‐enzyme reactors have been developed for highly efficient proteolysis in MS‐based proteomic analysis. This review focuses on the proteolysis step using protease‐immobilized reactors and rapid analysis of protein sequences. We describe the preparation of enzyme reactors by several techniques and protein digestion under unusual conditions. Analysis of posttranslational modifications by enzyme reactors prepared using our immobilization method is presented as a model application. Analysis systems using immobilized‐enzyme reactors are expected to become useful tools for proteomic studies and diverse applications in biotechnology.